Tensions and Challenges in the Management of Diversity and Inclusion in IT Services Multinationals in India - Donnelly, Rory (Human Resource Management, 2015)
Information technology (IT) services multinationals in India provide rich environments for the analysis of emerging patterns of diversity and inclusion management. Growing interest in this field of management has been accentuated by claims tabled by the business case and resource‐based rationales. However, challenges and tensions potentially undermine not only the viability of these assertions, but also the impact of diversity and inclusion interventions themselves. This article investigates the tensions and challenges faced by a sample of firms in India in relation to age, gender, and intra‐ and international diversity. The findings shed light on the implications of these tensions for HR management in these organizations, which need to be addressed if the claims put forward by the business‐ and resource‐based perspectives are to be realized and the management of diversity and inclusion is to be successfully aligned with business and HR strategies. © 2014 Wiley Periodicals, Inc.